MODELING AN INTER ORGANIZATIONAL INFORMATION SYSTEM TO PROMOTE ACCESS OF FINANCING FOR SMES IN AFRICA - (:unkn) unknown (My University, 2021)
The asymmetry of information, resulting from the agency theory, is an aspect that is much complained about by banks regarding SMEs in Africa; and is one of the main reasons for the lack of financing of which these SMEs are victims. The informal structure of the African SME is the main reason for this information asymmetry.Thus far, banks have been content to require African SMEs to adapt to their operations, such as having financial data that meets legal requirements, but this has only widened the gap between these two actors. This thesis proposes the modeling of an information system that is as well adapted to the constraints of banks as to those of the African SME, in order to promote the permanent sharing of information between these two actors. The modeled system would allow both banks to obtain qualitative and quantitative information on African SMEs and the latter to meet the requirements of banks to obtain the financing they need.
Keywords: African Research